From the information society to knowledge society - Tacca Huamán, Daniel Rubén (2014)
The phenomenon of globalization has brought great changes worldwide in the aspects of society as well as in economy, politics and education. The so-called "Information-based society" and its technological revolution have significantly contributed to the emergence of a new concept of production and education: the so-called "Knowledge Society", in which the development of content is not a main factor, as in the schools from traditional industrial societies, but primarily the development of capacities and skills